2015
DOI: 10.1016/j.neuropharm.2015.05.035
|View full text |Cite
|
Sign up to set email alerts
|

An adenosine kinase inhibitor, ABT-702, inhibits spinal nociceptive transmission by adenosine release via equilibrative nucleoside transporters in rat

Abstract: Adenosine kinase (AK) inhibitor is a potential candidate for controlling pain, but some AK inhibitors have problems of adverse effects such as motor impairment. ABT-702, a non-nucleoside AK inhibitor, shows analgesic effect in animal models of pain. Here, we investigated the effects of ABT-702 on synaptic transmission via nociceptive and motor reflex pathways in the isolated spinal cord of neonatal rats. The release of adenosine from the spinal cord was measured by HPLC. ABT-702 inhibited slow ventral root pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…3A–I), but not microglia (OX-42 + , Figs. 3J–R), consistent with a previous study [40]. Further analyses showed that while the percentage of ADK + astrocytes did not change (vehicle: 44.97% ± 12.23 vs. oxaliplatin: 44.49% ± 5.72; P =0.95; t -test; n=3/group), the cellular volume of astrocytes occupied by ADK (ADK + voxels/GFAP + voxels) increased 2-fold in the oxaliplatin-treated rats (vehicle: M2=0.20 ± 0.09 vs. oxaliplatin: M2=0.42 ± 0.08; P =0.048; t -test; n=3/group).…”
Section: Resultssupporting
confidence: 93%
“…3A–I), but not microglia (OX-42 + , Figs. 3J–R), consistent with a previous study [40]. Further analyses showed that while the percentage of ADK + astrocytes did not change (vehicle: 44.97% ± 12.23 vs. oxaliplatin: 44.49% ± 5.72; P =0.95; t -test; n=3/group), the cellular volume of astrocytes occupied by ADK (ADK + voxels/GFAP + voxels) increased 2-fold in the oxaliplatin-treated rats (vehicle: M2=0.20 ± 0.09 vs. oxaliplatin: M2=0.42 ± 0.08; P =0.048; t -test; n=3/group).…”
Section: Resultssupporting
confidence: 93%
“…Antinociceptive effects have been demonstrated for several different A 1 receptor activator types, specifically agonists in microglial cells, partial agonists and allosteric enhancers in acute and neuropathic pain models, and ADK inhibitors in chronic pain [58][59][60][61][62][63]. Moreover, a recent study on A 1 receptor-knockout (KO) mice, previously reported as mice with an increased nociceptive response, indicated that inosine behaves as an agonist for A 1 receptors, furnishing antinociceptive effects at a potency similar to adenosine itself [64], even though inosine may also act by competing with adenosine for nucleoside transport, thereby increasing its extracellular levels.…”
Section: Adenosine and Painmentioning
confidence: 99%
“…Inhibition of ADK is the most effective strategy for increasing the extracellular concentration of adenosine and occurs by potentiating intracellular concentrations of adenosine and supporting an outward driving gradient through passive ENTs (Keil and DeLander, ; Zhang et al , ). Pharmacological blockade of ADK activity in the CNS results in adenosine‐mediated inhibition of spinal nociceptive transmission via the ENT‐dependent release of adenosine (Otsuguro et al , ), and inhibitors of ADK are efficacious in rodent experimental neuropathic pain models (Kowaluk et al , ; McGaraughty et al , ). It is important to note that ADK expression shifts from neurons to astrocytes during postnatal development, and accordingly, astrocytes are central to this aspect of adenosine homeostasis (Studer et al , ).…”
Section: Introductionmentioning
confidence: 99%